Post Traumatic Stress Disorder and Its Associated Risk Factors among Trauma Patients Attending the Orthopaedic Wards and Clinics in Kota Bharu, Kelantan - Jaapar, Sharifah Zubaidiah Syed; Abidin, Zarina Zainan; Othman, Zahiruddin (Japan International Cultural Exchange Foundation, 2014)
Background: Posttraumatic stress disorder (PTSD) is prevalent among trauma patients seeking treatment. Objectives: This study aimed to evaluate the prevalence and associated risk factors of PTSD using the newly validated Malay Trauma Screening Questionnaire (TSQ-M). Methods: A total of 201 trauma patients attending the orthopaedic wards and clinics, Hospital Universiti Sains Malaysia (HUSM) and Hospital Raja Perempuan Zainab II (HRPZII) were recruited and the TSQ-M was administered to all participants. Results: A total of 50 (24.9%) of the trauma patients had PTSD based on TSQ-M using a cut-off score of 5. None of the risk factors were significantly associated with PTSD in this study. Female gender and lower education were, 2.00 and 1.82 times respectively, more likely to experience PTSD. Conclusion: PTSD is common affecting about a quarter of trauma patients attending the orthopaedic services. We need to maintain a high index of suspicion in trauma patients regardless of their socio-demographic and clinical characteristics.